Tracing the External Origin of the AGN Gas Fueling Reservoir - Raimundo, Sandra I. (Frontiers in Astronomy and Space Sciences, 2018)
Near-infrared observations of the active galaxy MCG--6-30-15 provide strong evidence that its molecular gas fuelling reservoir is of external origin. MCG--6-30-15 has a counter-rotating core of stars within its central 400 pc and a counter-rotating disc of molecular gas that extends as close as ~50 - 100 pc from the central black hole. The gas counter-rotation establishes that the gas reservoir in the centre of the galaxy originates from a past external accretion event. In this contribution we discuss the gas and stellar properties of MCG--6-30-15, its past history and how the findings on this galaxy can be used to understand AGN fuelling in S0 galaxies with counter-rotating structures.